KONTRIBUSI GURU BK DALAM PENCEGAHAN PERILAKU BULLYING DI SEKOLAH - Gusman Lesmana; Wida Melani; Dian Hikmah Br Tarigan (Jurnal Nirta : Inovasi Multidisiplin, 2026)
Bullying is a serious problem that threatens the well-being of students in schools. Guidance and Counseling (BK) teachers play a strategic role in preventing bullying behavior through various structured services and programs. This study aims to analyze the contribution of BK teachers in preventing bullying behavior in schools. The method used is a literature study by reviewing various relevant literature sources from 2017-2025. The results show that BK teachers contribute through orientation services, information, individual and group counseling, classical guidance, mediation, and collaboration with various parties. Comprehensive prevention programs, early detection, and handling of bullying cases are the primary responsibility of BK teachers. In conclusion, BK teachers have a vital role in creating a safe and bullying-free school environment through preventive, curative, and developmental approaches.